The Interplay of Technological Adaptability, Emotional Intelligence and Proactive Personality in Driving Entrepreneurial Behaviour: The Mediating Role of Alertness (Journal of Asian Development Studies, 2025)
This study examines the interplay between technological adaptability (TA), emotional intelligence (EI), and proactive personality (PP) in shaping entrepreneurial behaviour (EB), with entrepreneurial alertness (EA) as a mediator. Grounded in Social Cognitive Theory, Trait Activation Theory, and the Entrepreneurial Event Model, the research employs a quantitative, cross-sectional design to test seven direct and three indirect hypotheses. Data were collected from 450 university students in Gujranwala, Pakistan, using validated scales for each construct. Results from SPSS and Hayes' PROCESS macro analyses revealed that all direct hypotheses were supported: TA (β = 0.23, *p* < .001), EI (β = 0.28, *p* < .001), and PP (β = 0.31, *p* < .001) significantly predicted EA, which in turn strongly influenced EB (β = 0.35, *p* < .001). TA, EI, and PP also had direct effects on EB (β = 0.18, 0.15, and 0.22, respectively; *p* < .05). Mediation analysis confirmed that EA partially mediated the relationships between TA (β = 0.08, 95% CI [0.04, 0.13]), EI (β = 0.10, 95% CI [0.06, 0.15]), and PP (β = 0.11, 95% CI [0.07, 0.16]) with EB, explaining 20–25% of their total effects. The findings underscore the synergistic roles of technological, emotional, and personality factors in entrepreneurship, highlighting EA as a critical cognitive mechanism. Theoretical contributions include advancing integrated models of entrepreneurial cognition, while practical implications suggest targeted interventions for educators and policymakers to foster entrepreneurial mindsets. Limitations include the cross sectional design and regional sample, warranting future longitudinal and cross-cultural research.